Studi experimental penambahan minyak cengkeh pada bahan bakar pertalite terhadap kinerja dan emisi gas buang mesin tipe TV-1 - Sahrul Alam; Marthen Paloboran; Syafiuddin Parenrengi (TURBO [Tulisan Riset Berbasis Online], 2023)
This research is a laboratory experimental research using a TV-1 type testing machine. This study aims to determine the performance and exhaust emissions of a four-stroke motorcycle on pertalite fuel and fuel with a mixture of clove oil. The composition of the clove oil mixture used in the study. this is as much as 5%, 10%, 15%, 20% and 25% into pertalite fuel in units of milliliters (ml). Data collection uses observation techniques using observation tables to record the research results obtained. Data analysis techniques used descriptive analysis in the form of tables and graphs to present the research results. As for the research results from the analysis of engine performance, it was found that there was an increase in engine performance at low rpm with the addition of clove oil to pertalite fuel while for high rpm the greatest power was obtained on pure pertalite fuel. But for fuel consumption, the lowest consumption was found in the composition of 5% clove oil mixture. Whereas for exhaust emissions, the addition of clove oil to pertalite fuel for CO gas emissions can reduce emissions, namely the 10% clove oil mixture. For HC gas emissions, namely in a mixture of 5% and 10% clove oil. As for CO2 emissions, it can be seen that the higher the composition of the clove oil mixture, the emissions also decrease and the highest CO2 emissions are in the 5% clove oil mixture.